2009
DOI: 10.1097/iae.0b013e31818bcd30
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Domain Optical Coherence Tomography Imaging of the Detached Macula in Rhegmatogenous Retinal Detachment

Abstract: Dropout of the foveal photoreceptor inner and outer segment layers seen on spectral-domain optical coherence tomography imaging may be involved in incomplete recovery of visual acuity after successful retinal reattachment surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
74
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 31 publications
6
74
1
4
Order By: Relevance
“…These findings are consistent with those of experimental studies on animal model that showed more progressive outer retinal damage with greater height of the retinal detachment. 1,17,22 Accordingly, clinical studies, evaluating the morphology of the detached macula in primary RRD by SDOCT, showed that higher retinal detachment at the fovea was correlated with dropout of foveal photoreceptor IS/OS layer and worse postoperative VA. 23,24 Although we did not find any significant difference in VA outcome between eyes with persistent subfoveal fluid and those without subfoveal fluid, subgroup analysis revealed that in those eyes with residual subfoveal fluid, the disappearance of fluid was associated with an improvement in visual acuity. Our results, along with those of Benson et al 8 and Seo et al, 10 suggest that there is an association of delayed visual recovery in patients with macula-off RRD and residual SRF; however, the final visual outcome does not seem to be affected.…”
Section: Discussionmentioning
confidence: 49%
“…These findings are consistent with those of experimental studies on animal model that showed more progressive outer retinal damage with greater height of the retinal detachment. 1,17,22 Accordingly, clinical studies, evaluating the morphology of the detached macula in primary RRD by SDOCT, showed that higher retinal detachment at the fovea was correlated with dropout of foveal photoreceptor IS/OS layer and worse postoperative VA. 23,24 Although we did not find any significant difference in VA outcome between eyes with persistent subfoveal fluid and those without subfoveal fluid, subgroup analysis revealed that in those eyes with residual subfoveal fluid, the disappearance of fluid was associated with an improvement in visual acuity. Our results, along with those of Benson et al 8 and Seo et al, 10 suggest that there is an association of delayed visual recovery in patients with macula-off RRD and residual SRF; however, the final visual outcome does not seem to be affected.…”
Section: Discussionmentioning
confidence: 49%
“…Spectral-domain optical coherence tomography provided direct visualization of in vivo retinal morphology, allowing high-resolution observation of individual layers of the macula, thereby providing greater information for structural postoperative macular changes. Recent OCT studies have reported disruptions of photoreceptor microstructures and integrity of the outer retinal bands at the fovea in cases of macula-off RRD 5,[17][18][19]32,33 and other retinal diseases (e.g., macular hole 20,34 and central serous chorioretinopathy 35 ). In the present study, SD-OCT facilitated precise measurement of retinal layer thickness and evaluation of outer retinal band integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological changes that influence the outcome are, according to a recent study using spectral-domain optical coherence tomography, the dropout of the photoreceptor inner and outer layer segment in the fovea (Nakanishi et al 2009). The most recently described persistence of subretinal fluid in young macula-off patients treated with buckling surgery may contribute to a limited visual acuity long after an anatomical successful outcome (Abouzeid et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, at the end of the first decade of the 21st century, the documentation at the end of the surgical procedure (consisting of a detailed report and a drawing by the surgeon) would -in most cases -no longer be considered adequate to determine whether anatomical success as defined in this paper had been achieved. A spectral-domain OCT, for instance, is a significant progress in evaluating the reattachment of a previously detached macula before the patients' dismissal from the hospital (Nakanishi et al 2009). In this retrospective study, we were not able to determine the functional outcome of the retinal surgery conducted in our clinic because of the process of postoperative care in our region.…”
Section: Discussionmentioning
confidence: 99%